Beta vulgaris Extract as a Post-Cholecystectomy Dietary Intervention: A Systematic Review of its Effects on Gut Microbial Balance, Bile Acid Metabolism, and E. Coli/Lactobacillus Dynamics - Benedick Johanes Alvian; Sigit Adi Prasetyo; Yora Nintida (HM Publisher, 2025)
Background: Cholecystectomy, while a common surgical procedure, significantly alters bile acid dynamics and the gut microbiome, potentially leading to an imbalance favoring opportunistic pathogens like Escherichia coli over beneficial bacteria like Lactobacillus. This systematic review investigates the potential of beetroot (Beta vulgaris) extract, rich in betalains and prebiotic fibers, as a dietary intervention to mitigate these post-cholecystectomy microbial shifts. Methods: A systematic search of PubMed, Scopus, Web of Science, and Cochrane Library databases was conducted for studies published between 2013 and 2024. Keywords included